Random or Deterministic? Evidence from Indian Stock Market - Bora, Ivani; Tripathy, Naliniprava (International Journal of Economics and Financial Issues, 2016)
This study investigates the presence of long memory and non-linear dynamics in Indian stock market returns for a period of 19 years from May 1997 to May 2016 by using Rescaled Range (R/S) method and V-statistics. The empirical findings suggest that Indian stock market shows a high degree of long-range persistence and future stock price can be predicted. The study also finds the presence of multiple non-periodic cycles in the data generating process, with a maximum cycle length of 3.7 years. This study is quite helpful to the participants of the capital markets to improve their portfolio performance by taking efficient strategy before making investment decision Keywords: R/S Analysis, V-Statistic, Non-linear Dynamics JEL Classifications: C22, C53, G14